Microbial communities and substrate properties influence the fate of a human pathogen in horticultural substrates with different peat content - Müller, Antje; Schmidt, Jasmin; Maiberg, Verena; Gehring, Oscar; Schikora, Adam (Frontiers in Horticulture, 2025)
The use of peat alternatives in horticulture is part of an important strategy aiming at the reduction of CO2 emission and the preservation of natural wetlands. Today, different components are proposed as replacement of peat in plant growing media, very often as a heterogeneous mixture of different components. Their diverse origin is responsible for their particular physicochemical characteristics as well as the specific microbial activity. The latter brings, however, the risk of contamination with potentially pathogenic organisms, both to plants and humans. In this study, we assessed the microbial compositions of four different commercially available plant growing substrates, which ranged from 100% to 0% peat. Using amplicon sequencing of the 16S rRNA gene fragment and the ITS region, we revealed the microbial differences among those substrates and the only very minor changes in peat-reduced or peat-free substrates observable over the course of 12 weeks under greenhouse conditions. In addition, we monitored the persistence of the externally added human pathogen Salmonella enterica serovar Typhimurium (S. Typhimurium) by direct CFU enumeration on a selective medium. Results obtained in this study suggest that although S. Typhimurium was not able to persist in three of the tested substrates, in the peat-free 2 substrate its persistence may be substantially supported. Our results strengthen therefore the notion that in addition to the structural differences among the different tested substrates, the microbial community composition may add to their functional diversity. This underlines the necessity of considering microbial community compositions regarding the replacement of peat in horticultural substrates.